Management of hepatitis B virus infection after liver transplantation - Jiménez-Pérez, Miguel (World J Gastroenterol, 2015)
Chronic hepatitis B virus (HBV) infection is responsible for up to 30% of cases of liver cirrhosis and up to 53% of cases of hepatocellular carcinoma. Liver transplantation (LT) is the best therapeutic option for patients with end-stage liver failure caused by HBV. The success of transplantation, though, depends on receiving prophylactic treatment against post-transplant viral reactivation. In the absence of prophylaxis, liver transplantation due to chronic hepatitis B (CHB) is associated with high rates of viral recurrence and poor survival. The introduction of treatment with hepatitis B immunoglobulins (HBIG) during the 1990s and later the incorporation of oral antiviral drugs have improved the prognosis of these patients. Thus, LT for CHB is now a universally accepted option, with an estimated 5 years survival of around 85% vs the 45% survival seen prior to the introduction of HBIG. The combination of lamivudine plus HBIG has for many years been the most widely used prophylactic regimen. However, with the appearance of new more potent oral antiviral agents associated with less resistance (e.g., entecavir and tenofovir) for the treatment of CHB, new prophylactic strategies are being designed, either in combination with HBIG or alone as a monotherapy. These advances have allowed for more personalized prophylaxis based on the individual risk profile of a given patient. In addition, the small pool of donors has required the use of anti-HBc-positive donors (with the resulting possibility of transmitting HBV from these organs), which has been made possible by suitable prophylactic regimens.